THE EFFECT OF ORGANIC MATERIALSFROM CATFISH Clarias sp.CULTURE ON BIOMASS (Tubifexsp) CULTIVATION WITH THE RECIRCULATIONSYSTEM - Putra, Widodo; Pamukas, Niken Ayu; Rusliadi, Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was aimed to determine the organic matter produced from catfish waste with different stocking densities that are best for the increase of biomass and the number of silk worms that are maintained with a recirculation system. The research method used was the experimental method and the design used was a non-factorial Completely Randomized Design with 4 levels of stocking solid treatment namely 100 catfish / m3 (P1), 150 catfish / m3 (P2), maintenance of catfish 200 / m3 (P3). The results showed that organic matter produced from different catfish stocking densities had a significant effect (P <0.05) on individual biomass and growth. The highest biomass value and individual growth were found in 200 tail / mstocking density3 (P3)with an average of 137.3 g and an increase in individuals with an average of 49,302 individuals. Based on the results it can be concluded that organic matter produced from stocking density of different catfish culture can increase individual biomass and growth.Keywords:Tubifexsp, Stocking Density, biomass, individual growth, materials organic.